The Inductance of the Rectangular Contours - M. Y. Antipov; G. N. Tsitsikyan (Известия высших учебных заведений России: Радиоэлектроника)
The influence of two rectangular contours with their various configurations is considered. The formulas for calculation of mutual induction are received and based on them the dependences of the coefficient of mutual induction of the distance between the contours with various shapes are built. The connection of the coefficients of mutual induction for a variety contours is installed.